Work and family attitudes of urban Filipino adolescents - Dela Paz, Mary Grace Villacorte; Chi, Cleofe L.; De Guzman, Ligaya S.; Nava, Fe' Josefa G.; Ronquillo, Carolyn U. (2008)
A researcher-made questionnaire and FGD were used to find out if the Filipino adolescents' attitudes regarding work, family, and work-family relationship had evolved given the changes in the socio-cultural context. Results showed that the urban Filipino adolescents have modern attitudes. They are equally influenced by gender and SES. There is an association between their work attitudes and their occupational interests and marrying age. However, there was no association between their family and work-family relationship attitudes and their occupational interests and marrying plans.
"Summer 2005."
Thesis (M.A. Education : Guidance)--University of the Philippines, Diliman.
Keywords: Teenagers -- Philippines -- Quezon City -- Attitudes; Teenagers -- Philippines -- Marikina City -- Attitudes; Teenagers -- Family relationships -- Philippines -- Quezon City; Teenagers -- Family relationships -- Philippines -- Marikina City; High school seniors -- Philippines -- Quezon City -- Attitudes; High school seniors -- Philippines -- Marikina City -- Attitudes